Impeachment da presidente Dilma Rousseff : espetacularização e legitimação na mídia da Veja - Silva, Elba Silveira Chagas (2018)
In the media space, there is a dispute of political and ideological forces that intervene directly in the process of discursive formation of the subjects that are affected by a discursive exteriority of the language. According to Piovezani Filho (2003), politics and media have been related since the middle of the last century. Therefore, the politicization of the media is not something new, what is new is the fact that a new way of dealing with information / events under the aegis of spectacularization has emerged. Therefore, this research is inserted in the field of Discourse Analysis (AD), and we develop it through the qualitative-interpretative method, making a vertical analysis of the discursive cuts and relating them to the socio-historical context, seeking to work the registered meanings in and by language. As a general objective, we intend to show how the discursive materiality of Veja magazine established, constructed and naturalized, in social space, the sense of impeachment through a discourse ideologically marked and crossed by relations of power. The analyzes are about the impeachment event of former president Dilma Rousseff, and the corpus is made up of five editions of Veja Magazine from the years 2015 and 2016, a period in which the production of discourses that contributed significantly to the acceptance, legitimation and concretization of the historical-discursive fact - impeachment. Based on the idea of Gregolin (2003), which emphasizes the media as being responsible for acting as spokesperson for the interests of the people, it is shown in this study how the senses are woven, traversed by Discursive Formations (FDs) which represent ideologies that challenge the subjects. Today, more than ever, the media integrate political discourses into their discursive practice in reporting events, and this interferes in the course of history, in the reader's / viewer's way of thinking and acting, given that the facts are amenable to numerous interpretations. As a theoretical framework, scholars like Althusser (1985), Brandão (2012), Foucault (2014, 2016), Gregolin (2003), Gadet and Hak (2010), Pêcheux and Fuchs (1975), Orlandi 2007, 2009, 2011, 2012), among others. In the face of the analyzes, it is concluded that the journal in its speeches embarked on the task of naturalizing impeachment with constant involvements of interpellation / assujeitamento, in addition to that the subject enunciador reflected ideological practices coming from interdiscourses that were affiliated to certain ideological positions, demonstrating, with this, bias in dealing with impeachment. In this context, from the discursive formation of the Veja, it is perceived that, through the silencing of other discourses, the magazine maintained a posture of ultra-right, attending to the interests of a certain class, and did not demonstrate a position of neutrality in addressing facts of politics Brazilian society, aiming, therefore, to undermine the public image of Dilma and of the Workers' Party (PT), to which she is affiliated. In addition, the politicized media field acted with its discourses docilizando "the bodies", through the production of mechanisms of control, as shown by Foucault (2014).